The Agility Profile of Phase C Students Participating in Futsal Extracurricular Activities at SDN 053 Cisitu Bandung City - Nurjanah, Siti Sonia; Ghalib, Najwan Muhammad; Putri, Wulandari; Anira, Anira (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research explores the agility of Phase C students participating in Futsal extracurricular activities at SD Negeri 053 Cisitu, Bandung City. This research is descriptive quantitative research with a survey method. The sampling technique researchers use is purposive sampling, namely, Phase C students who participated in Futsal extracurricular activities with 23 boys. The data collection technique in this research used an agility measurement instrument for Phase C students from the Ministry of Education and Culture. Data were analyzed using descriptive percentage techniques. The results of data analysis show that the number of agility levels of Phase C students who took part in Futsal extracurricular activities in the poor category was two students (8.7%), in the moderate category was four students (17.4%), in the good category was 12 students (21.7%), and in the excellent category. as many as five students (52.2%). The conclusion of this research shows that the level of agility of Phase C students who participate in Futsal Extracurricular activities is in the